Perancangan dan Evaluasi Sistem Informasi Klinik (Si-Klinik) Avicena Berbasis Website menggunakan System Usability Scale (SUS) - Auf Affan (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2022)
Technology that is increasingly advanced and developing at this time can be utilized and applied in all fields, including the health sector including clinics to provide effective and efficient services to the community. Avicenna Clinic is one of the clinics in Bantul Regency that gets a lot of patient visits for treatment. However, the service still uses a manual system starting from registration, storing patient data, administering drugs, and paying fees paid by patients. This causes problems in the form of taking a long time to register patients, difficult to find patient medical records, especially if the patient comes without a visiting card and information cannot be provided immediately if needed. Based on these problems, this study aims to design and design a website-based clinical information system to improve the quality of service to patients. In this study, the SUS questionnaire was used. The research flow begins with creating a clinical application UI design using the Adobe Photoshop CS3 application and the draw.io application. The number of respondents involved in this study amounted to 15 respondents using random sampling technique. The results of the study using the SUS questionnaire obtained an average score of 80 which was included in the grade or "Good" rating which indicated that the system was good and acceptable.